A Multicenter, International Collaborative Study for AJCC-Staging of Retinoblastoma: Metastasis-Associated Mortality - Tomar, Ankit Singh (2020)
Purpose: To evaluate the ability of the 8th edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual to estimate metastatic and mortality rates for children with retinoblastoma (RB). Design: International, multicenter, registry-based retrospective case series. Participants: A total of 2190 patients from 18 ophthalmic oncology centers from 13 countries over 6 continents. Methods: Patient-specific data fields for RB were designed and selected by subcommittee. All patients with RB with adequate records to allow tumor staging by the AJCC criteria and follow-up for metastatic disease were studied. Main Outcome Measures: Metastasis-related 5- and 10-year survival data after initial tumor staging were estimated with the KaplaneMeier method depending on AJCC clinical (cTNM) and pathological (pTNM) tumor, node, metastasis category and age, tumor laterality, and presence of heritable trait. Results: Of 2190 patients, the records of 2085 patients (95.2%) with 2905 eyes were complete. The median age at diagnosis was 17.0 months. A total of 1260 patients (65.4%) had unilateral RB. Among the 2085 patients, tumor categories were cT1a in 55 (2.6%), cT1b in 168 (8.1%), cT2a in 197 (9.4%), cT2b in 812 (38.9%), cT3 in 835 (40.0%), and cT4 in 18 (0.9%). Of these, 1397 eyes in 1353 patients (48.1%) were treated with enucleation. A total of 109 patients (5.2%) developed metastases and died. The median time (n ¼ 92) from diagnosis to metastasis was 9.50 months. The 5-year KaplaneMeier cumulative survival estimates by clinical tumor categories were 100% for category cT1a, 98% (95% confidence interval [CI], 97e99) for cT1b and cT2a, 96% (95% CI, 95e97) for cT2b, 89% (95% CI, 88e90) for cT3 tumors, and 45% (95% CI, 31e59) for cT4 tumors. Risk of metastasis increased with increasing cT (and pT) category (P < 0.001). Cox proportional hazards regression analysis confirmed a higher risk of metastasis in category cT3 (hazard rate [HR], 8.09; 95% CI, 2.55e25.70; P < 0.001) and cT4 (HR, 48.55; 95% CI, 12.86e183.27; P < 0.001) compared with category cT1. Age, tumor laterality, and presence of heritable traits did not influence the incidence of metastatic disease. Conclusions: Multicenter, international, internet-based data sharing facilitated analysis of the 8th edition AJCC RB Staging System for metastasis-related mortality and offered a proof of concept yielding quantitative, predictive estimates per category in a large, real-life, heterogeneous patient population with RB.